Gamificação, motivação e engajamento no trabalho: um estudo qualitativo de múltiplos casos - Miri, Daniel Hank (My University, 2020)
The motivation and engagement of an employee in the workplace are essential for carrying out their activities and consequently generating results for the company. Gamification, in turn, is the use of activities, applications or software with game design elements. Gamification is a recent topic in academic research and this is an opportunity to expand studies in this area by providing knowledge for the academic and organizational spheres. The general objective of this study was to analyze how the application of gamification promotes employee motivation and engagement in the work environment. An exploratory qualitative research was carried out through a study of multiple cases with the participation of 4 companies. For each study, the results were generated in the triangulation of data from the semi-structured interviews, available documentation and reports of direct or participant observation with the analysis in the NVivo 11® software. The survey showed the perception of gamification focused on the company and the perception of gamification focused on the employee. Gamification for motivation and engagement at work was limited in cases 1 (platform), 2 (website) and 3 (escape game), case 4 obtained the best result with a mobile application. The study showed the understanding that the correct planning and application of gamification with the elements of scoring, feedback and adequate rewards are necessary to promote motivation and engagement in the work environment. These elements not only characterize a gamified tool, but also enable the proper progress of activities in the work cycle that involves companies, developers / instructors, managers and employees / users.
A motivação e o engajamento de um funcionário no local de trabalho são essenciais para a realização de suas atividades e consequentemente a geração de resultados para a empresa. Por sua vez, a gamificação é o uso de atividades, aplicativos ou softwares com os elementos de design de jogos. A gamificação é um tema recente na pesquisa acadêmica sendo esta uma oportunidade para ampliar os estudos nesta área proporcionando conhecimento para o âmbito acadêmico e organizacional. O objetivo geral deste estudo foi analisar como a aplicação da gamificação promove a motivação e o engajamento dos funcionários no ambiente de trabalho. Houve a realização de uma pesquisa qualitativa exploratória por meio de um estudo de múltiplos casos com a participação de 4 empresas. Para cada estudo, os resultados foram gerados na triangulação de dados das entrevistas semiestruturadas, documentação disponível e relatórios de observação direta ou participante com a análise no software NVivo 11®. A pesquisa apontou a percepção da gamificação voltada para a empresa e a percepção da gamificação voltada para o funcionário. A gamificação para motivação e engajamento no trabalho foi de forma limitada nos casos 1 (plataforma), 2 (site) e 3 (escape game), o caso 4 obteve o melhor resultado com um aplicativo de celular. O estudo mostrou o entendimento que o correto planejamento e aplicação da gamificação com os elementos de pontuação, feedback e recompensas adequados são necessários para promover a motivação e o engajamento no ambiente de trabalho. Estes elementos não só caracterizam uma ferramenta gamificada como possibilitam o devido andamento das atividades no ciclo de trabalho que envolve empresas, desenvolvedores/instrutores, gestores e funcionários/usuários.
Keywords: Motivação no trabalho; Jogos de empresas; Employee motivation; Management games